1995
DOI: 10.1103/physreva.51.513
|View full text |Cite
|
Sign up to set email alerts
|

Spin-orbit effects in aluminum photoionization

Abstract: The eigenchannel R-matrix approach, in conjunction with the multichannel quantum-defect theory and the LS~j j recoupling frame transformation, is used to calculate the photoionization spectrum of Al i below the 3s3p P ionization threshold (photon energies in the range 0.44 ( tub ( 0.98 Ry). Relativistic channel mixing is incorporated in the calculations by a recoupling frame transformation and by the inclusion of experimental 6ne-structure threshold energies. This mixing enables autoionization of resonances wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…causing a shift in the resonance structures con-1s22p 1@2, 3@2 ), verging there. These e †ects are well illustrated in a recent calculation on Al [17], using an eigenchannel R-matrix approach for photoionization with spinÈorbit e †ects and a core polarization model potential.…”
Section: Introductionmentioning
confidence: 64%
“…causing a shift in the resonance structures con-1s22p 1@2, 3@2 ), verging there. These e †ects are well illustrated in a recent calculation on Al [17], using an eigenchannel R-matrix approach for photoionization with spinÈorbit e †ects and a core polarization model potential.…”
Section: Introductionmentioning
confidence: 64%
“…Photoionization cross sections for Ar have also been obtained theoretically using the ab-initio R-matrix approach [19], which was extended to use multi-configuration Hartree-Fock (MCHF) orbitals for the description of residual states of Ar II [20]. A detailed description of how photoionization cross sections are determined in LS-coupling has been given previously [21,22].…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…Theoretical and experimental studies for photoabsorption of the Al + ion have been performed by several authors [5][6][7][8][9][10][11]. Recent measurements of absolute cross sections for Al + ion were performed by West et al [2], where they reported strong peaks in the photoionization cross section for the Al + ion from 20 to 26 eV as being due to the significant influence of fourth-order radiation.…”
Section: Introductionmentioning
confidence: 99%